P106 Clinical outcomes of patients diagnosed with non-specific pleuritis following medical thoracoscopy. (12th November 2019) - Lin, Z; Rajaratnam, T; Slaven, K; Karia, S; Pulimood, T; Knolle, M; Herre, J
Abstract : Background: Medical thoracoscopy (MT) is the gold standard investigation for exudative pleural effusions of cryptic origin. A diagnosis of non-specific pleuritis (NSP) however has unclear long-term outcomes, with some NSP patients harbouring occult mesotheliomas. The reported percentage of pleural malignancy following NSP ranges from 3–18% in studies with varied MT and biopsy approaches. Objectives: We retrospectively analysed the rate of pleural malignancy following an NSP diagnosis from a standardised MT procedure in a UK population from the east of England, a region with a high recorded mesothelioma rate. Methods: Between March 2009 to March 2019, 729 patients with exudative pleural effusions underwent standardised rigid MT. Full thickness biopsies were taken from multiple sites. We defined NSP by the same histological criteria described by Davies et al . 2010. Results: A definitive diagnosis was reached in 689 patients (95%). Patients with known malignancies, CTDs and TB were then excluded. 213 patients (29%) were diagnosed with NSP and followed up for a mean of 40±31 months (range 0–114). 13 (6%) subsequently developed mesotheliomas and 1 an adenocarcinoma after a mean interval of 135±128 days. The false negative rate for pleural malignancy was 2.86%. Conclusion: This is the largest single centre series of patient outcomes for NSP described to date. The percentage of false negatives was lower than predicted from most previous studies. We speculate this could be due to differences in population including asbestos exposure, sample size, diagnostic latency, biopsy approach and/or histological analysis. There is a need to develop better risk stratification for future malignancy in NSP to allow targeted follow-up of patients. We are pursuing immunohistological means of doing this.